A European randomised controlled trial of the addition of etoposide to standard vincristine and carboplatin induction as part of an 18-month treatment programme for childhood (≤16 years) low grade glioma: a final report - Gnekow, Astrid K.; Walker, David A.; Kandels, Daniela; Picton, Susan; Perilongo, Giorgio; Grill, Jacques; Stokland, Tore; Sandstrom, Per Eric; Warmuth-Metz, Monika; Pietsch, Torsten; Giangaspero, Felice; Schmidt, René; et al. (Elsevier, 2017)
Background